Recent Advances in Commerce, Management, and Tourism - Kumar, Prem; Feston, Baby Niviya; Parivara, Swetha Appaji; Singh, Sumit Kumar (Recent Advances in Commerce, Management, and Tourism, 2023)
The edited book, "Rethinking Commerce, Management, and Tourism - Post-COVID New Normal," presents a comprehensive exploration of the transformative impact of the COVID-19 pandemic on these critical sectors. As the world grappled with unprecedented challenges, businesses, policymakers, and scholars faced the imperative to adapt and innovate. This volume assembles a diverse range of perspectives, offering multidisciplinary insights, real-world case studies, and practical guidance. Topics such as social media marketing, Caravan tourism, medical tourism, entrepreneurship, sustainability, consumer behaviour, human resource management, financial markets and instruments are a few among others. With a commitment to advancing knowledge and fostering resilience, this book aims to inspire fresh ideas, stimulate discussions, managerial implications and contribute to the collective effort to revive and rebuild the business. It serves as a compass for navigating the evolving dynamics of commerce, management, and tourism in the aftermath of the pandemic.